2004
DOI: 10.1103/physrevc.69.034610
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of kinetic energy fluctuations due to expansion

Abstract: Global equilibrium fragmentation inside a freeze out constraining volume is a working hypothesis widely used in nuclear fragmentation statistical models. In the framework of classical Lennard Jones molecular dynamics, we study how the relaxation of the fixed volume constraint affects the posterior evolution of microscopic correlations, and how a non-confined fragmentation scenario is established. A study of the dynamical evolution of the relative kinetic energy fluctuations was also performed. We found that as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Beside statistical descriptions, there are microscopic frameworks that directly treat the dynamics of colliding systems such as the family of semi-classical simulations based on the nuclear Boltzmann equation (the Vlasov-UehlingUhlenbeck (VUU), Landau-Vlasov (LV), Boltzmann-Uehling-Uhlenbeck (BUU) or Boltzmann-Nordheim-Vlasov (BNV) codes [144,145,146,147]), classical molecular dynamics (CMD) [121,148,149,150], quantum molecular dynamics (QMD) [113,114,115], fermionic molecular dynamics (FMD) [117], antisymmetrized molecular dynamics (AMD) [116,118,119] and stochastic mean field approaches related to simulations of the Boltzmann-Langevin equation [122,123,124,126,127,128]. Boltzmann type simulations follow the time evolution of the one body density.…”
Section: Dynamical Descriptions Of Multifragmentationmentioning
confidence: 99%
“…Beside statistical descriptions, there are microscopic frameworks that directly treat the dynamics of colliding systems such as the family of semi-classical simulations based on the nuclear Boltzmann equation (the Vlasov-UehlingUhlenbeck (VUU), Landau-Vlasov (LV), Boltzmann-Uehling-Uhlenbeck (BUU) or Boltzmann-Nordheim-Vlasov (BNV) codes [144,145,146,147]), classical molecular dynamics (CMD) [121,148,149,150], quantum molecular dynamics (QMD) [113,114,115], fermionic molecular dynamics (FMD) [117], antisymmetrized molecular dynamics (AMD) [116,118,119] and stochastic mean field approaches related to simulations of the Boltzmann-Langevin equation [122,123,124,126,127,128]. Boltzmann type simulations follow the time evolution of the one body density.…”
Section: Dynamical Descriptions Of Multifragmentationmentioning
confidence: 99%
“…This means that in this model, contrary to the Lattice case [35], the two coexisting phases at the transition temperature can be populated even in an ensemble which strongly constrains the volume of the system. In particular the two characteristic signals of a first order phase transition in a finite system, namely bimodality in the canonical ensemble and negative heat capacity in the microcanonical one, can be observed even in the isochore ensemble [30,31]. For stronger size constraints (smaller average volumes) the caloric curve is monotonic, the microcanonical constraint reduces fluctuations well below the canonical limit, and the mean square radius increases linearly with the energy.…”
Section: B Microcanonical Thermodynamicsmentioning
confidence: 85%
“…We will use the example of a classical Lennard-Jones system [29] to evaluate some chosen observables for a statistical isolated system subject to a radial flow. Molecular dynamics simulations on the same system have already shown that flow enhances partial energy fluctuations [30] and at the same time can act as a heat sink [31,32], cooling the system and thus preventing it to reach high temperatures. We will show that in the statistical limit it can also act as a heat bath, since the relaxation of the microcanonical constraint allows the isolated system to explore a larger configuration space.…”
Section: Introductionmentioning
confidence: 99%
“…(7) is well verified. At t ≈ 20t 0 the system is still dense and homogeneous in first approximation [15] (see fig.1). We can then make the assumption that at t ≈ 20t 0 ≡ t 1 the initial condition (1) still describes the observed distribution with the extra constraint of a collective flow p · r (t 1 ) = 0,…”
Section: Statistical Treatment Of the Expansion Dynamicsmentioning
confidence: 93%
“…An interesting observable to study the freeze-out properties of the system is given by the normalized kinetic energy fluctuation A K = N σ 2 K / K 2 . This quantity shows a saturation when the sharing between kinetic and potential energy finishes, which physically corresponds to the formation of surfaces within the system, which in turn implies a chemical stabilization of the cluster properties [15]. The behavior of this fluctuation with time is displayed for four representative energy states in the upper part of Figure 1.…”
Section: Choice Of the Comparison Timementioning
confidence: 99%